ANALYSIS OF THE DIFFUSION OF SCIENTIFIC RESEARCH ON RIVER BASINS (WATERSHEDS) IN BRAZIL - BORDIN, D.; GABRIEL FILHO, L.R.A.; PUTTI, F.F.; CREMASCO, C.P.; GOES, B.C.; SATOLO, E.G. (Revista Brasileira de Engenharia de Biossistemas, 2014)
River basins or watershed areas have suffered great impact due to deforestation and pollution, which in turn also comprises decrease in the volume of water in rivers involved. Current research overviews scientific literature related to the theme "Watershed", published between 2002 and 2012, and assess the scientific contribution. The research method consists of an exploratory bibliographical survey of Brazilian research on the above-mentioned subject retrieved from the database Web of Science (WoS). Data treatment was conducted through a bibliometric analysis to identify institutions with greater representation in publications and citations by region. The bibliometric analysis was performed with software developed in Delphi language and types of Microsoft Excel® software, Ucinet®, NetDraw® and ArcGIS® that enabled the development of graphical representations related to publications and citations by regions. When the analysis of bibliometric indicators was analyzed, the most productive institutions were mapped and the impact and visibility of their publications and relationships that occurred in collaboration between researchers from major institutions were evaluated. Research related to the theme "Watershed" has its largest production between physically close institutions. This fact shows the need for government action, through investments, for the integration of researchers from different regions to construct a national coverage for these networks. Finally, the Southeast Region of Brazil should be underscored due to its production of more than 50% of publications and citations out of the national total.